2022
DOI: 10.1172/jci153792
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ACVR1 antibodies exacerbate heterotopic ossification in fibrodysplasia ossificans progressiva (FOP) by activating FOP-mutant ACVR1

Abstract: Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disorder whose most debilitating pathology is progressive and cumulative heterotopic ossification (HO) of skeletal muscles, ligaments, tendons, and fascia. FOP is caused by mutations in the type I BMP receptor gene ACVR1 , which enable ACVR1 to utilize its natural antagonist, activin A, as an agonistic ligand. The physiological relevance of this property is underscored by the fact that HO in FOP is exquisitely dependent on act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…We showed that while JAB0505 effectively inhibits ligand-dependent BMP signaling through wild-type ACVR1 and ACVR1(R206H) in certain cell contexts in vitro, JAB0505 also functions as a weak agonist of ACVR1(R206H), thereby replacing the essential function of activin A in injury-induced skeletal lesion formation in FOP mice ( 4 , 6 ). Recent independent studies confirmed the ability of anti-ACVR1 antibodies to profoundly worsen HO in FOP mice, and further demonstrated that the HO-exacerbating effects were dependent on antibody bivalency and their ability to cluster ACVR1(R206H)-containing receptor complexes ( 14 ). Collectively, these studies raise serious safety and efficacy concerns for the use of anti-ACVR1 antibodies as a treatment modality to block ligand-receptor interactions in patients with FOP.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We showed that while JAB0505 effectively inhibits ligand-dependent BMP signaling through wild-type ACVR1 and ACVR1(R206H) in certain cell contexts in vitro, JAB0505 also functions as a weak agonist of ACVR1(R206H), thereby replacing the essential function of activin A in injury-induced skeletal lesion formation in FOP mice ( 4 , 6 ). Recent independent studies confirmed the ability of anti-ACVR1 antibodies to profoundly worsen HO in FOP mice, and further demonstrated that the HO-exacerbating effects were dependent on antibody bivalency and their ability to cluster ACVR1(R206H)-containing receptor complexes ( 14 ). Collectively, these studies raise serious safety and efficacy concerns for the use of anti-ACVR1 antibodies as a treatment modality to block ligand-receptor interactions in patients with FOP.…”
Section: Discussionmentioning
confidence: 88%
“…Understanding the pathological effects of anti-ACVR1 antibodies will require follow-up investigations that explore the connection between antibody-mediated receptor clustering ( 14 ), downstream biochemical sequelae, and the tissue-level cellular effects reported here. Regardless of mechanism, these studies demonstrate that anti-ACVR1 antibodies characterized to date profoundly exacerbate disease progression in FOP mice, highlighting the importance of using genetically and physiologically relevant mouse models and cell types to evaluate potential therapeutic candidates for FOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fascinating FOP story takes another twist in this issue of the JCI . Given the clear evidence that activin A binding to FOP-variant ACVR1 drives HO in FOP, both Regeneron and David Goldhamer’s laboratory developed anti-ACVR1 antibodies as potential therapeutics for FOP ( 10 , 11 ). In both cases, in vitro testing in cell lines overexpressing either WT or FOP-mutant ACVR1 confirmed that such antibodies blocked both WT and mutant ACVR1 signaling.…”
Section: Anti–activin a Antibodies Cause Ho In Fopmentioning
confidence: 99%
“…Aykul, Huang, et al ( 10 ) developed three anti-ACVR1 monoclonal antibodies (mAb 1, mAb 2, and mAb 3); in vitro, all three demonstrated high affinity for human and mouse ACVR1, lacked binding to related BMP receptors, and blocked Smad1/5/8 signaling in cells overexpressing ACVR1. Like JAB0505, the Regeneron antibodies stimulated R206H ACVR1 signaling and promoted HO in FOP mice.…”
Section: Anti–activin a Antibodies Cause Ho In Fopmentioning
confidence: 99%